Interventional practices for social deficits in ASD: A systematic literature review (International Seven Journal of Multidisciplinary, 2024)
Autism Spectrum Disorder, which is characterized by repetitive, stereotyped behavioral patterns, restricted interests, impaired communication and social interaction, is a neurodevelopmental disorder with an undefined etiology. This study aims to analyze the practices used for social deficits in autism in order to ascertain their effectiveness. Methodologically, this is a systematic review of the literature in the following databases: PubMed, LILACS and SCIELO, using the following descriptors: "Social skills" and "Autism" and "Intervention". A total of 934 articles were found and 17 were selected for analysis, based on the inclusion and exclusion criteria and quality assessment using the Pedro Scale. The articles were analyzed qualitatively, and an average score of 8 was obtained, indicating adequate methodological quality for inclusion in this study. The conclusion is that there is a massive use of behavioral interventions that seek to complement the interventions already used, with the aim of enhancing the results achieved, and that a gap was found in the absence of studies aimed at individuals with a higher level of support in ASD.